The Popular Music Aesthetic Education at Grade 11, Zhengzhou Linghang Experimental School, Henan Province, The People’s Republic of China - Yufei, Wu; Supattarachiyawong , Watcharapong (Journal of Buddhist Education and Research (JBER), 2025)
This study examined popular music aesthetic education for Grade 11 students at Zhengzhou Linghang Experimental School, Henan Province, The People’s Republic of China, with a focus on applying the Kodály teaching method. The primary aim was to enhance students’ ability to distinguish between high-quality and inferior musical works, while also promoting their overall development. The research was conducted from July 2024 to June 2025, employing a mixed-methods approach that integrated literature analysis, surveys, interviews, classroom observations, pilot testing, and other data collection methods. Both qualitative and quantitative methodologies were utilized for in-depth data analysis. The research findings indicate the following: First, students’ ability to critically evaluate popular music significantly improved, with a deeper and more diverse understanding of high-quality music. They moved beyond surface-level features to consider various dimensions such as melody, lyrical meaning, social value, and emotional resonance. Second, students actively engaged in class activities, demonstrating high enthusiasm and initiative. Significant progress was observed in their overall music literacy, including rhythm perception, listening skills, and instrumental performance. Third, with the application of the Kodály teaching method, students’ music memory, physical coordination, and attention required for piano performance were effectively strengthened, resulting in a deeper and more solid understanding of music knowledge. Fourth, the course introduced music works from diverse regions and cultural backgrounds, enriching students’ musical knowledge, broadening their international perspectives, and enhancing their intercultural communication skills. This effectively promoted a comprehensive understanding of music and global cultural diversity. This study provides valuable insights for the reform of high school popular music aesthetic education courses and demonstrates the feasibility and effectiveness of applying the Kodály teaching method in this field.